2019
DOI: 10.1249/mss.0000000000002162
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Intensity Continuous Training or High-Intensity Interval Training with or without Resistance Training for Altering Body Composition in Postmenopausal Women

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(103 citation statements)
references
References 44 publications
3
99
0
1
Order By: Relevance
“…When the HIIT group was considered separately, however, our stratified analysis failed to detect a HIIT‐induced effect on abdominal FM loss in postmenopausal women. Another study performed by our laboratory also showed that a 12‐week HIIT programme (60 × 8 s at 80–90% of peak heart rate, 12 s active recovery) performed three times a week in 10 postmenopausal women resulted in a significant decrease in total (−3.06% ± 4.2) and abdominal (−7.4% ± 2.8) FM (Dupuit et al., 2020). Thus, a larger sample of postmenopausal women would have been probably necessary to reach a significant threshold in this meta‐analysis and more data would be needed to establish whether oestrogen deficiency requires a greater total amount of interval training to achieve a comparable remodelling of body composition.…”
Section: Discussionmentioning
confidence: 67%
“…When the HIIT group was considered separately, however, our stratified analysis failed to detect a HIIT‐induced effect on abdominal FM loss in postmenopausal women. Another study performed by our laboratory also showed that a 12‐week HIIT programme (60 × 8 s at 80–90% of peak heart rate, 12 s active recovery) performed three times a week in 10 postmenopausal women resulted in a significant decrease in total (−3.06% ± 4.2) and abdominal (−7.4% ± 2.8) FM (Dupuit et al., 2020). Thus, a larger sample of postmenopausal women would have been probably necessary to reach a significant threshold in this meta‐analysis and more data would be needed to establish whether oestrogen deficiency requires a greater total amount of interval training to achieve a comparable remodelling of body composition.…”
Section: Discussionmentioning
confidence: 67%
“…Our group already demonstrated that HIIT is a time-efficient and safe exercise modality for loosing total and (intra-) abdominal fat mass in post-menopausal women. [10][11][12] However, the mechanisms leading to a greater fat mass loss in HIIT vs MICT are still unclear. HIIE stimulates catecholamine production leading to lipolysis and higher post-exercise free fatty acid availability.…”
Section: Discussionmentioning
confidence: 99%
“…The first one [60 × (8-s cycling − 12-s recovery) at 80%-90% HR max ] has been extensively tested by our group and by others in pre-and post-menopausal women. [10][11][12]25 The second one [10 × 1 minutes at 80%-90% HR max − 1-min recovery] is regularly used in different population types (ie, normal weight, overweight, obese people, young or older, trained, or untrained subjects). [26][27][28] We hypothesized that for the same exercise duration, the longer active phase of HIIE (10 minutes for HIIE 2 vs 8 minutes for HIIE 1) could induce greater post-exercise VO 2 uptake and/or fat utilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations